IMPROVING OF GREEN COVER AND EXTERIOR LANDSCAPE DESIGN OF BAGHDAD UNIVERSITY " JADRIYAH CAMPUS" - & Kamel, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The universities on-campus external spaces represent the urban ecological view, which should be characterized by some environmental parameters that achieve comfort and self-vitality and promote social interactions among university personals. The University of Baghdad, aljadriah campus, was selected as an urban ecosystem for further practical study. Data were collected according to a field survey for selected outer spaces in addition to visual and locational observations. Forms of the questionnaire were randomly distributed among university’s students, data were collected in Microsoft Excel and analyzed using the Statistical Analysis System (SAS), and means were compared according to the least significant differences (LSD) test. Results showed that walking, comfort, and relaxation were the most significant among the parameters used in this study with a weight of 84.50 and 83.50, respectively. One of the most important employments of vegetation in university’s outer spaces is highlighting the differences in landscape elements and provide a broad spectrum of colors, shadings, and linings with weights of 94.67, 87.33, and 80.00, respectively. As for the shelters, they preferred the separated and stripped ones above walking and seating areas. Water elements also played a significant role in contributing to the landscape vitality in addition to its importance to the surrounding ecosystem. It was preferred to be seen as fountains with a percentage of 47.37%. Plants natural shading was also preferred by 50% when compared to artificial shading. Finally, 37.89% preferred that walkways are paved with natural stones.